(3OQQ GdCUOGa aj aVd GdSGOI GdCTQGas - (3YHO GdLhGO Hf NVQ GdTQHjfj, GdTQHjfj,J (B1128 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi EUWai eMeOkG Udi Gddg Ydjg hSde Ydi SGFQ GdeNdhbGJ s
(3BNQgG (B:s
(3bGd eDdag (B: (3hhGab GdaQGZ ef Qbeg hJSWjQg hcJGHJg hJMQjQg NJGe Pi GdMLI GdMQGe SfI KeGfjIhYTQjf heGFI HYO GdCda hMSHfG Gddg hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B276s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs